2019
DOI: 10.1021/jacs.9b01800
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding and Cleavage Modes of Shishijimicin A

Abstract: Although shishijimicin A and its extreme potencies against an array of cancer cell lines have been known for more than a decade, its assumed DNA-cleaving mechanism has not been substantiated as yet. Herein we report studies that reveal binding and scission of doublestranded DNA by shishijimicin A. The results of these studies support the proposed hypothesis that DNA strand scissions are caused by 1,4-benzenoid diradicals formed by Bergman cycloaromatization of the enediyne core of shishijimicin A upon activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…One crucial feature of enediynes is their ability to abstract H atoms from the deoxyribose backbone and cause DNA cleavage. For natural enediynes, even at low concentrations, they can significantly lead to double-strand (ds) DNA cleavage . The ds DNA cleavage mode, which is much more difficult for cells to repair than the single-strand (ss) DNA cleavage, can culminate in efficient self-programmed cell death (apoptosis), achieving the high cytotoxicity to tumor cells for chemotherapy.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…One crucial feature of enediynes is their ability to abstract H atoms from the deoxyribose backbone and cause DNA cleavage. For natural enediynes, even at low concentrations, they can significantly lead to double-strand (ds) DNA cleavage . The ds DNA cleavage mode, which is much more difficult for cells to repair than the single-strand (ss) DNA cleavage, can culminate in efficient self-programmed cell death (apoptosis), achieving the high cytotoxicity to tumor cells for chemotherapy.…”
Section: Resultsmentioning
confidence: 84%
“…As the concentration of EDY-C or EDY-F increases, a decrease of Form I (and even Form II) and a concurrent increase of Form III of pUC19 are observed. The high percentage of ds DNA cleavage (Figure C) originates from binding of enediyne molecules in the minor groove of DNA and cutting both strands of DNA in a single event. Meanwhile, the possibility that multiple binding/cleavage events take place with more than one drug molecules involved should not be ruled out either .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-antitumor agent intercalation binding plays an important role in cell proliferation and can induce DNA conformational changes. It is known that the circular dichroism (CD) spectra of the B-form of DNA has a positive band at about 275 nm due to base stacking and a negative band of similar magnitude at about 245 nm due to base right-hand helicity .…”
Section: Results and Discussionmentioning
confidence: 99%
“…As DNA intercalators, their planar aromatic moieties insert between adjacent base pairs, which decreases the DNA helical twist and length of the DNA strand, and disrupts important processes such as DNA replication, transcription, and repair . Recently, many DNA intercalators have been used as potential lead compounds due to their inhibitory effect on the growth of cancer cells. , Besides, bivalent ligands formed by the tethering of two DNA intercalating agents by an appropriately designed spacer have proved more effective inhibitors than their corresponding monomers by increasing the number of binding sites and improving the interaction of ligands with their corresponding receptors. We recently reported that a bivalent ligand based on isoquinoline-3-carboxylic acid exhibited improved antitumor activity compared to isoquinoline-3-carboxylic acid alone …”
Section: Introductionmentioning
confidence: 99%